Os BRICS na perspectiva geopolítica: uma análise cientométrica de 2001 a 2010 - Prado, Marcos Aparecido Rodrigues do [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The contemporary world has a geopolitical construction in which the emerging market countries have been highlighted in the conjunction of global power. In this configuration, a group of countries was organized and has strengthened its representation in the international scene. Brazil, Russia, India, China and South Africa are the countries that share the expectations of a global power characterized by multipolarity. The governments of the four first mentioned countries articulated the formalization of a geopolitical bloc with strategic relevance for action against the international scene. Thus, the BRICS bloc was formed as a political organization that seeks to promote consorted actions covering economic, social and strategic development. In 2001, the acronym was coined by the english economist Jim O'Neill English as a result of a study that showed the four most promising countries among emerging economies. In 2006 it was begun a process of political integration among the four countries. The success of periodic governmental summits that followed led to the formalization of the BRIC bloc in 2009. And in 2010, the group expanded with the accession of South Africa as a full member. Since then, the block became officially termed as BRICS. It is with interest in such a geopolitical construction that this study is based on scientometry to analyze the economic and social indicators and their correlations with indicators of scientific production. Thus, the research aims to survey and analyze the data on scientific publications indexed in Scopus basis of the four countries that make up the genuine BRICS group, Brazil, Russia, India and China. Also, the scope of the study comprises the presentation of the concepts and applications of indicators as well as the identification of relevant features of the geopolitical scenario and scientific context in which the BRICS are inserted. The method used was the comparative study between indicators raised...

O mundo contemporâneo dispõe de uma construção geopolítica em que os países de economia emergente têm se destacado na conjunção do poder global. Nesta configuração, um grupo de países se organizou e tem fortalecido sua representação no cenário internacional. Brasil, Rússia, Índia, China e África do Sul são as nações que compartilham das expectativas de um poder global caracterizado pela multipolaridade. Os governos dos quatro primeiros países mencionados articularam a formalização de um bloco geopolítico com relevância estratégica para atuação frente ao cenário internacional. Assim, o bloco BRICS foi constituído como organismo político que visa promover ações consorciadas que abrangem o desenvolvimento econômico, social e estratégico. Em 2001, o acrônimo foi cunhado pelo economista inglês Jim O’Neill como resultado de um estudo que apontou os quatro países mais promissores entre as economias emergentes. Em 2006, deu-se início a um processo de integração política entre os quatro países. O sucesso das periódicas cúpulas governamentais que se seguiram ocasionou à formalização do bloco BRICs no ano de 2009. E, em 2010, ocorreu a iniciativa de expansão do grupo com a adesão da África do Sul como membro efetivo. Desde então, o bloco passou a ser denominado oficialmente como BRICS. É com interesse em tal construção geopolítica que este estudo se baseia na cientomentria para analisar os indicadores econômicos e sociais e suas correlações com os indicadores de produção científica. Desta forma, a pesquisa objetiva levantar e analisar os dados relativos às publicações científicas indexadas na base Scopus dos quatro países que integram o genuíno grupo BRICS, ou seja, Brasil, Rússia, Índia e China. Também, compõe o escopo do estudo a apresentação dos conceitos e aplicações dos indicadores, assim como a identificação das características relevantes do cenário geopolítico e do...
Keywords: Bibliometria; Pesquisa econômica; Geopolitica - Pesquisa; BRICS Indicadores 2001-2010